Cooperative Protein Allosteric Transition Mediated by a Fluctuating Transmission Network. Issue 17 (15th September 2022) - Post, Matthias; Lickert, Benjamin; Diez, Georg; Wolf, Steffen; Stock, Gerhard
Graphical abstract: Highlights: We investigate the time-dependent progression of allostery in a bistable protein. The microscopic mechanism can be revealed by a correlation analysis. Allosteric communication is mediated via a network of intra-protein contacts. Allosteric transitions are cooperative, i.e., all contacts need to change in unison. The cooperative process is fluctuation-driven as in an Ising-type model. Abstract: Allosteric communication between distant protein sites represents a key mechanism of biomolecular regulation and signal transduction. Compared to other processes such as protein folding, however, the dynamical evolution of allosteric transitions is still not well understood. As an example of allosteric coupling between distant protein regions, we consider the global open-closed motion of the two domains of T4 lysozyme, which is triggered by local motion in the hinge region. Combining extensive molecular dynamics simulations with a correlation analysis of interresidue contacts, we identify a network of interresidue distances that move in a concerted manner. The cooperative process originates from a cogwheel-like motion of the hydrophobic core in the hinge region, which constitutes an evolutionary conserved and flexible transmission network. Through rigid contacts and the protein backbone, the small local changes of the hydrophobic core are passed on to the distant terminal domains and lead to the emergence of a rare global conformational transition. As in an Ising-type model, the cooperativity of the allosteric transition can be explained via the interaction of local fluctuations.